Advantages of being diligent: lessons learnt from umbilical venous catheterisation in neonates - Abiramalatha, Thangaraj (BMJ Case Rep, 2016)
Umbilical venous catheters (UVCs) are commonly used in neonatal units. Abdominal radiograph, taken soon after the insertion, is used to confirm the correct placement of the catheter. However, as demonstrated by our case series, complacency when an initial UVC is normally positioned can lead to detecting UVC-related complications very late. We describe cases of three neonates where, despite the initial UVC being confirmed to be well positioned, the patients developed life-threatening complications, including liver haematoma, left atrial thrombus and pericardial effusion causing cardiac tamponade. The routine use of point of care echocardiography helped in the early diagnosis of these complications. We suggest repeated echocardiographic screening at regular intervals in all newborn babies requiring UVCs, to ensure that the catheter is maintained in the proper position and for the early detection of catheter-related complications.